Pengaruh Tagline Aje Kendor Yang Disampaikan Oleh Unsur Pimpinan Melalui Saluran Primer Terhadap Perilaku Kerja Pegawai Aparatur Sipil Negara Di Pemerintah Kota Serang - Sunjaya, Sunjaya; Kurniawati, Rd. Nia Kania; Muldi, Ail (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this research is to determine and analyze the simultaneous direct influence of the Aje Kendor tagline message, message source and message channel) on the work behavior of state civil servants in the Serang City Government This research used quantitative methods with a sample size of 76 respondents. In this research, it was studied using multiple regression analysis. Regression analysis is a method or technique for analyzing research hypotheses to test whether there is a relationship between the independent variable and the dependent variable, to support the strengthening of hypothesis testing analysis, researchers use SPSS version 24 statistical calculations in the form of Correlation Coefficient Test, Determination Coefficient Test and Regression Equation Test so that actions and solutions can be identified. The results of the regression analysis research obtained significant values ​​of, x¹ 0.063, x² 0.080 > 0.05 and x³, 0.032 < 0.05 and the results of the partial regression test (t test) obtained t test values ​​calculated at x¹ 1.885, x² 1.776 < t table 1.992 means there is no influence and x³, -2.191 > 1.992 is greater than t table. This means there is a positive influence on the work behavior of State Civil Service employees in the Serang City Government.